Factors Associated With Postmarketing Research for Approved Indications for Novel Medicines Approved by Both the FDA and EMA Between 2005 and 2010: A Multivariable Analysis. Issue 5 (24th February 2018) - Zeitoun, Jean‐David; Ross, Joseph S.; Atal, Ignacio; Vivot, Alexandre; Downing, Nicholas S.; Baron, Gabriel; Ravaud, Philippe
Abstract : We examined whether drug‐related characteristics—conditions, development, manufacturers, revenues—were associated with postmarketing research in terms of the number of trials and total population to be enrolled. We included 63 drugs, corresponding to 3, 867 postmarketing trials of approved indications. On multivariable analysis, both the number of postmarketing trials and population to be enrolled were associated with expected length of treatment (ratio of means (RoM) = 2.35 and RoM = 8.65) and number of patients in pivotal trials (RoM = 1.11 and RoM = 1.25 per thousand patients). The number of postmarketing trials was increased for drugs approved with surrogate endpoints (RoM = 2.19), generating high revenues (RoM = 1.08 per billion dollars) and addressing greater disease burden (RoM = 1.90 per hundred million disability‐adjusted life years). The population to be included was increased for drugs approved after an increased number of pivotal trials (RoM = 1.82) and those unaffected by safety concerns (RoM = 2.63). Postmarketing trials seem to be driven both by medical and market factors.